Journalist Professionalism in Radio Broadcasting: Integrating Ethical Reporting, Accuracy, and Editorial Commitment - Sulistian Damayanti; Miladiyah; Nur Abnisah; Khadijah; Susanti Hasibuan (Al-Qalam Institue, 2026)
This study aims to analyze journalist professionalism in maintaining ethical reporting and accuracy in radio broadcasting. The research employed a qualitative approach using a descriptive method. Data were collected through in-depth interviews with key informants, including the editor-in-chief, journalists, and radio management. The study focused on the implementation of journalistic ethics, reporting accuracy as an indicator of professionalism, and the factors that support and hinder professional journalistic practices. The findings reveal that journalistic ethics are implemented through the principles of independence, balance, separation of facts from opinions, respect for sources, and compliance with professional ethical and broadcasting standards. In terms of accuracy, journalists apply systematic verification procedures, source confirmation, and structured news script preparation based on the 5W+1H framework. Although journalists face challenges such as time constraints, limited human resources, and the rapid flow of digital information, ethical standards and accuracy remain higher priorities than broadcasting speed. The study implies that journalist professionalism is shaped not only by individual competence but also by an effective editorial system and strong institutional commitment to ethical standards and verification practices. These factors play a crucial role in maintaining media credibility and public trust.